La difficile gestione degli orsi “problematici”: il caso dell’esemplare M49 - GIUSEPPE GARZIA (2022)
This paper is aimed at studying the policies for the managment of “troubled” bears, which have been adopted by the Autonomous Province of Trento (PAT) over the last few years in the light of legal framework of general (State and supranational) and local nature (provincial regulations and PACOBACE) . Namely, The analysis is addressed to the difficult legal issue regarding the bear known as M49. Such a matter shows the difficulty met by the PAT both to apply properly the different regulations in force, which refer to the protection of Ursus Arctos, and to create an atmosphere which fosters a peaceful relations between bears and humans.